Desarrollo de la redacción durante el aprendizaje del idioma inglés frente a la redacción en español en los estudiantes de octavo semestre de la carrera de Comunicación Social - Ramirez Zuñiga, Odalis Giscela (2020)
This research paper aims to carry out an analysis on the wording and the importance that students should have in terms of learning the English language because future communicators who can deliver content are currently required in both languages and facilitates them in terms of social development. The techniques used through research are indirect observation, the interview, which is conducted to teachers of the Technical University of Babahoyo from which data of great importance were obtained on how the students develop in writing and learning another language in this case English, in addition a qualitative survey is carried out through the form of Google Drive which allows to know first-hand information on the subject in question. Throughout this research are shown several peculiarities and notable reviews that need future professionals is important to note that the studied.